2018
DOI: 10.1111/ecot.12188
|View full text |Cite
|
Sign up to set email alerts
|

Does government R&D stimulate or crowd out firm R&D spending? Evidence from Chinese manufacturing industries

Abstract: We examine whether receiving a government R&D grant stimulates or crowds out a firm’s own R&D spending in Chinese manufacturing industries. Using a database that spans the population of large and medium size privately owned Chinese manufacturing firms for the period from 2007 to 2011, a matching estimator and a matching and difference in‐differences estimator, we find a large firm R&D promoting effect of government R&D: receiving a government R&D grant led to a 4 to 9‐million‐yuan increase in a firm’s own R&D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…Based on the previous mentioned studies, as output variable, the environmentally adjusted multifactor productivity growth measured (in %) is used. As inputs, to analyse countries efficiently in using human sources in R&D and public/private R&D spending, following variables were used:  R&D personnel -RDPER (per thousand labour force) that are commonly expected as a key to higher productivity (Zhang et al, 2003);  Business enterprise expenditure on R&D -BERD (in % of GDP) because private sector innovation and R&D activities and expenditures substantially contribute to sustainable productivity and growth (Hud & Hussinger, 2015);  Government expenditure on R&D -GOVERD (in % of GDP) that support firms' innovation and cooperation that could lead to other positive effects influencing countries productivity (Hu & Yongxu, 2019). In research, also the control variable was engaged.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the previous mentioned studies, as output variable, the environmentally adjusted multifactor productivity growth measured (in %) is used. As inputs, to analyse countries efficiently in using human sources in R&D and public/private R&D spending, following variables were used:  R&D personnel -RDPER (per thousand labour force) that are commonly expected as a key to higher productivity (Zhang et al, 2003);  Business enterprise expenditure on R&D -BERD (in % of GDP) because private sector innovation and R&D activities and expenditures substantially contribute to sustainable productivity and growth (Hud & Hussinger, 2015);  Government expenditure on R&D -GOVERD (in % of GDP) that support firms' innovation and cooperation that could lead to other positive effects influencing countries productivity (Hu & Yongxu, 2019). In research, also the control variable was engaged.…”
Section: Methodsmentioning
confidence: 99%
“…Based on RBV, subsidies are the resources allocated to firms by the government to reduce innovation risk and overcome other innovation barriers (Einiö, 2014; Howell, 2017). Prior research studies have mainly focused on how the subsidies directly affect firms innovation and also found that the subsidies indeed trigger R&D investment (Hottenrott and Lopes-Bento, 2014; Hu and Deng, 2019), stimulate innovation cooperation or activity (Beck et al , 2016; Szücs, 2018) and foster innovation performance (Bronzini and Piselli, 2016; Deng et al , 2019; Jia and Ma, 2017; Sung, 2019).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Particularly, governments often offer the subsidies for firm innovation to aim at incentivizing innovation and pushing an optimal allocation of innovation resources (Beck et al , 2016). Despite the prevalence and importance of the subsidies to firm innovation (Hu and Deng, 2019; Jia and Ma, 2017; Sung, 2019; Szücs, 2018), some studies have paid increasing attention to their crowding-out effects. The crowding-out effects are usually referred to the following two phenomena: The use of one decreases the use or participation of the other (Bahal et al , 2018; Chakraborty et al , 2018; Huffman and Bognanno, 2017; Weche, 2018); and The use of one eliminates the benefits or positive roles of using the other (Cao and Lumineau, 2015; Fong et al , 2019; Gubler et al , 2016; Hunt and Fund, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…a szakirodalom és a statisztikák elemzése alapján megállapítható, hogy Kína látványos eredményeket ért el a "digitális nagy ugrásra" és a mesterséges intelligenciára alapozott gazdaságfejlesztési stratégiájával. a gazdaság fejlettségét tükröző elsődleges ("felszíni") mutatók történelmileg páratlanul rövid idő alatt kiemelkedő mértékben javultak, ami még annak ellenére is lenyűgöző teljesítmény, hogy az elemzők többsége joggal hívta fel a figyelmet arra, hogy ezt az eredményt talán lassabban, de mindenképpen jóval kevesebb erőforrással, hatékonyabban is el lehetett volna érni (Hong és szerzőtársai [2016], Howell [2017], Wei és szerzőtársai [2017]ellentétes véleményt képvisel Hu-Yongxu [2019]). nem csupán a "felszíni" mutatók tükrözik, hogy a kínai gazdaság a fejlett tudásgazdaságokhoz közelít: az utóbbi fél évtizedben egyre inkább láthatóvá vált, hogy kezdenek beérni az intenzív fejlődés érdekében tett extenzív erőfeszítések 22 gyümölcsei.…”
Section: Feldolgozóipar öSszes Exportunclassified